Controlling the bandgap in graphene/h-BN heterostructures to realize electron mobility for high performing FETs. Issue 50 (19th June 2017) - Behera, Sushant Kumar; Deb, Pritam
Abstract : Electric field induced field-effect mobility and nontrivial Z 2 topological phase transition in graphene sandwiched by h-BN bilayers. Abstract : Two dimensional van der Waals heterostructures have shown promise in electronic device applications because of their high charge carrier mobility, large surface area and large spin conductance value. However, it still remains a great challenge to design heterolayers with an electric field driven tunable electronic bandgap and stable geometry to obtain high electron mobility. Motivated by the inherent relationship between electronic bandgap and topological phases, we systematically explore the effect of external electric field on a model heterostructure of graphene sandwiched between boron nitride (h-BN) bilayers, an h-BN/graphene/h-BN heterostructure. We have studied the topological phase transition in the presence of spin orbit coupling (SoC) using density functional theory (DFT) supported by a tight-binding (TB) based Hamiltonian. The heterostructure system exhibits a nontrivial Z 2 quantum spin Hall phase accompanied by bandgap closing and reopening, driven by the external applied electric field. The quantum phase transitions follow a w-like shape in the case of SoC with a clear distinction between topological and normal insulating phases. The electric field induced switching nature between nontrivial and trivial phases creates a potential platform for quantum spin Hall states in the layered structure. This field driven switching nature helps to increase the number of edge transport channels parametrically with quantized electrical conductance. The merits of this behavior of the layered heterostructure are beneficial for its use as a topological field-effect-transistor.